Resource potential and maturity estimates of Euphausia superba in East Antarctica - Maschette, Dale; Wotherspoon, Simon; Murase, Hiroto; Kelly, Nat; Ziegler, Philippe; Swadling, Kerrie M.; Kawaguchi, So (Frontiers in Marine Science, 2025)
The East Antarctic krill fisheries are spread across two Divisions of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR), Division 58.4.1 between 80-150°E and Division 58.4.2 between 30-80°E. Each of these Divisions is further divided into East and West subregions with separate catch limits. In 2019, CCAMLR agreed to a revised krill fishery management strategy recommended by the Scientific Committee. This strategy consists of setting catch limits for Euphausia superba using three combined approaches; 1) an acoustic biomass estimate, 2) a precautionary harvest rate derived from a stock assessment and 3) a spatial allocation of catch limits based on overlap of predator needs. Using recent survey data we estimate 50% length at maturity for E. superba to be 41.67 mm and 42.29 mm for Divisions 58.4.1 and 58.4.2 respectively. In both areas females were estimated to reach 50% maturity at a smaller length than males. Using these updated estimates of E. superba length at maturity and a new implementation of the Generalized Yield Model (the Grym), we estimate precautionary harvest rates for krill in Divisions 58.4.1 and 58.4.2-East ranging between 0.0854 - 0.1201. These calculated harvest rates were then applied to the biomass estimates from recent surveys to estimate total precautionary catch limits for E. superba in Divisions 58.4.1 (391,754 tonnes) and 58.4.2 East (640,872 tonnes). These catch limits are based on biomass estimates from a 2019 survey conducted by Japan in Division 58.4.1 and a 2021 survey conducted by Australia in Division 58.4.2 East.